Comparison of the Effectiveness Between Mindfulness Therapy and Cognitive Behavioral Therapy in Treating Anxiety Disorders - Cahyono, Intim; Sulaeman, Ridawati; Hanum, Lathifah; karyono, Septin Maisharah; Mubarok, Ahmad Shofi (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The growing complexity of anxiety disorders, a common mental health problem, significantly affects individuals' quality of life. In an effort to address this disorder, mindfulness therapy and cognitive-behavioral therapy (CBT) have become an increasing focus of research. However, the comparative effectiveness between these two therapeutic approaches is still a matter of debate in the scientific literature. The purpose of this study was to compare the effectiveness of mindfulness therapy and cognitive behavioral therapy in overcoming anxiety disorders. The research method used was a systematic review of relevant empirical studies that have been conducted in this field. Data from these studies were comprehensively analyzed to evaluate the relative effectiveness of the two therapeutic approaches. The results showed that both mindfulness therapy and cognitive behavioral therapy have significant benefits in reducing anxiety disorder symptoms. However, there are differences in the approach and focus of each therapy. Mindfulness therapy emphasizes on self-awareness of thoughts and feelings without judging them, while cognitive-behavioral therapy focuses on changing negative thought patterns and harmful behaviors. In addition, some studies have shown that cognitive-behavioral therapy can provide faster results especially in addressing acute anxiety symptoms, while mindfulness therapy tends to be more effective in the long run. The conclusion of this study is that both mindfulness therapy and cognitive-behavioral therapy can be effective options in treating anxiety disorders, depending on individual needs and preferences. The selection of the appropriate therapy should take into account individual characteristics, the severity of the anxiety disorder, and the treatment context. A combination or integration between the two types of therapy may also be a promising approach in improving treatment outcomes for individuals with anxiety disorders.